Serum levels of miR-21, miR-23a, miR-142-5p, and miR-126 in chronic failure with reduced ejection fraction: a case-control study - Evin, Lukas; Sigutova, Radka; Sulc, Patrik; Kufova, Eliska; Branny, Marian; Vaclavik, Jan; Stejskal, David (Frontiers in Cardiovascular Medicine, 2025)
BackgroundMicroRNAs (miRNAs) are small non-coding RNA molecules that function as gene regulators in physiological processes, including proliferation, differentiation, and apoptosis. Various microRNAs have been linked to pathophysiological events associated with heart disease. In this case-control study, we investigated the levels of human miR-21, miR-23a, miR-142-5p, and miR-126 among heart failure patients with reduced ejection fraction (HFrEF), compared to healthy control participants.MethodsWe prospectively enrolled clinically stable patients with heart failure (HF) and left ventricle ejection fraction (LVEF) ≤ 40%, and healthy individuals. MicroRNAs were analyzed from venous blood, using a microRNA enzymatic immunoassay (miREIA) method. Plasma miRNA levels were compared between HFrEF patients and healthy individuals, using non-parametric tests.ResultsWe enrolled 73 patients with HFrEF (86% males, mean age: 66.3 ± 10.7 years) and 99 healthy subjects (36% males, mean age: 44.7 ± 15.9 years). All four assayed miRNAs exhibited significantly higher median levels in heart failure patients compared to healthy controls: miR-21p, 243 pmol·l−1 vs. 14 pmol·l−1; miR-23a-3p, 705 pmol·l−1 vs. 119 pmol·l−1; miR-142-5p, 1,695 pmol·l−1 vs. 146 pmol·l−1; and miR-126-3p, 528 pmol·l−1 vs.21 pmol·l−1 (P ≤ 0.001 for all). The analyzed miRNA levels did not differ according to age, weight, height, or body mass index. No miRNA levels correlated with NTproBNP levels.ConclusionOur findings revealed that the levels of miR-21-5p, miR-23a-3p, miR-142-5p,and miR-126-3p were significantly higher among HFrEF patients compared to healthy controls. Further exploration of these miRNAs may lead to new diagnostic, prognostic, and therapeutic options for HF patients.